PENGARUH LINGKUNGAN KERJA PADA MASA PANDEMI COVID-19 TERHADAP KONDISI KESEHATAN SERTA IMPLIKASINYA TERHADAP PRODUKTIVITAS KERJA GURU SEKOLAH DASAR - Dara Sagita Triski; Imas Soemaryani; Wa Ode Zusnita Muizu (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
The purpose of this study was to examine how the online work environment affects the health of teachers and how it affects their productivity at the Integrated Islamic Elementary School (SD-IT). Path analysis method is an analytical approach used in this study. Teachers have faced a number of challenges as a result of the Covid-19 pandemic, including some degree of disruption for both teachers and students. Basically, maintaining a smooth teaching and learning process (PBM) that results in high productivity requires more than just a healthy work environment and also depends on the health of teachers. According to the measurement of the effectiveness and efficiency of teacher skills, there has been a decline in teacher productivity in online learning, which in the 2020-2021 school year ranged from only 70-75%. According to research findings, the work environment has a negative impact of 19.27% ​​on teacher productivity in terms of their physical and mental health. The priority for improvement is the work environment, followed by the creation of health conditions that will increase teacher productivity.